Municipal budgets in India: comparison across five cities - Sekhar, Sita; Bidarkar, Smita (1999)
Budgets reflect the calibre of planning and the priorities of municipal corporations. Analysis of municipal budgets is a means to determine the extent to which poor quality of services is a result of inadequate availability and inefficient use of resources by city agencies. With increased focus on decentralisation and devolution of funds, more attention should be paid to the analysis of municipal budgets. This article makes a comparative study of the municipal budgets of five large cities in India - Ahmedabad, Bangalore, Chennai, Mumbai and Pune - over a six-year period of time, giving useful insights into resource mobilisation and utilisation, allocation patterns and trends in important sources of revenue and in expenditure on important sectors across cities. - Reproduced
Keywords: Local finance - India; Local finance